2020
DOI: 10.1111/all.14689
|View full text |Cite
|
Sign up to set email alerts
|

Food‐dependent NSAID‐induced hypersensitivity (FDNIH) reactions: Unraveling the clinical features and risk factors

Abstract: Background In up to 70%–80% of patients with a suspected non‐steroidal anti‐inflammatory drug hypersensitivity (NSAIDH), challenge tests with the culprit drug yield negative results. On the other hand, there could be a NSAIDH overdiagnosis when anaphylaxis is the clinical manifestation. We hypothesize that some negative NSAID challenge tests and an overdiagnosis of NSAIDH occur in patients with food‐dependent NSAID‐induced hypersensitivity (FDNIH). Methods We studied 328 patients with a suspected acute NSAIDH.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
(178 reference statements)
0
10
0
Order By: Relevance
“…NSAIDs may act as a co-factor inducing or aggravating food-dependent exercise-induced urticaria/angioedema or anaphylaxis, and the related phenotype is now defined as food-dependent NSAID-induced hypersensitivity (FDNIH) and classified as a subgroup of NSAID-H for adults. 81,118 In this case, food or an NSAID does not induce a reaction exclusively; however, exercise 4 to 6 hours preceded by simultaneous ingestion of the specific food and the NSAID induces the reaction. In some cases, solitary food ingestion would result in a mild reaction such as oral allergy syndrome or contact urticaria.…”
Section: Changes In Classification For Children and Adolescentsmentioning
confidence: 97%
“…NSAIDs may act as a co-factor inducing or aggravating food-dependent exercise-induced urticaria/angioedema or anaphylaxis, and the related phenotype is now defined as food-dependent NSAID-induced hypersensitivity (FDNIH) and classified as a subgroup of NSAID-H for adults. 81,118 In this case, food or an NSAID does not induce a reaction exclusively; however, exercise 4 to 6 hours preceded by simultaneous ingestion of the specific food and the NSAID induces the reaction. In some cases, solitary food ingestion would result in a mild reaction such as oral allergy syndrome or contact urticaria.…”
Section: Changes In Classification For Children and Adolescentsmentioning
confidence: 97%
“…157 Improvements in genomics have facilitated assessing the rela- ) and NSAIDs hypersensitivity (Figure 7 ). 156 Recently, Sanchez-Lopez et al 161 have reported that 16% of patients with suspected NSAID hypersensitivity could be further diagnosed as suffering from food-dependent NSAID-induced hypersensitivity, with LTP and gliadin being the main culprit food allergens.…”
Section: Biomarkers Of Drug Hypersensitivit Ymentioning
confidence: 99%
“…Recent advances have facilitated the analysis of the complete transcriptome, revealing associations between different gene expression (POSTN, CNKSR, SPTBN2, ADORA3) and NSAIDs hypersensitivity (Figure7) 156. Recently, Sanchez-Lopez et al161 have reported that 16% of patients with suspected NSAID hypersensitivity could be further diagnosed as suffering from food-dependent NSAID-induced hypersensitivity, with LTP and gliadin being the main culprit food allergens.Non-immediate reactions are characterized by a wide range of clinical manifestations driven by different mechanisms. The heterogeneity of NIDHR makes it essential to identify biomarkers for accurate diagnosis.…”
mentioning
confidence: 99%
“…93 In contrast, sensitization to some cereal and peach allergens (lipid transfer protein) is a high-risk factor to nonsteroidal anti-inflammatory drugs anaphylaxis, without any cross-reactivity identified. 94 The first-line treatment of any type of anaphylaxis, whatever the mechanism, is adrenaline (epinephrine). As far as therapeutic tools are concerned, the avoidance of the drug is the only efficient action when possible.…”
Section: Conclusion and Therapeutic Avenuesmentioning
confidence: 99%